Legal Protection of Customers Against the Loss of Funds in Bank BCA: A Civil Law Analysis and the Role of the Financial Services Authority - Ernawati, Atis Ika; Ramadhan, M. Jasuli; Wanda Ndapa, Damianus; Syarif Arkiang, Bachder; Miftahuddin, Miftahuddin (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the banking sector has a legal obligation to safeguard customers’ funds with a high standard of prudence, yet in reality, cases of fund loss still frequently occur, including at Bank BCA. This situation raises doubts about the effectiveness of the legal protection available to customers when their rights are harmed. This study aims to examine the forms of legal protection for customers from the perspective of civil law and to evaluate the role of the Financial Services Authority (OJK) in resolving and restoring losses caused by fund loss in banks. This article falls under library research with a qualitative approach. The methodology used is normative legal research. The findings show that civil law provides a basis for protection through compensation mechanisms arising from breach of contract or unlawful acts, which may be claimed by customers against the bank. On the other hand, OJK serves as a regulator and external supervisor that plays an important role in ensuring justice for customers through regulation, supervision, and alternative dispute resolution mechanisms outside the court via LAPS SJK. The synergy between civil law instruments and the role of OJK has proven to be an essential instrument in providing legal certainty while maintaining public trust in the banking system.